An Introduction to Experimental Design and Statistics for Biology - Heath, David (UCL Press, 1995)
Suitable for biologists, this book provides an introduction to the ideas of sampling, experimental design, and statistical analysis. It also provides various things required in an introductory statistics course for biology undergraduates. It introduces statistics with the use of diagrammatic explanations and a range of biological examples.